2011
DOI: 10.1080/00220388.2010.509784
|View full text |Cite
|
Sign up to set email alerts
|

Is Corruption Really Bad for Inequality? Evidence from Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 50 publications
(38 reference statements)
4
30
0
Order By: Relevance
“…For instance, corruption can alter the composition of social spending to benefit the rich at the expense of the poor, leading to higher inequality [21]. In line with this argument, studies have found a positive relationship between institutions and income inequality.…”
Section: The Relationship Between Institutions and Inequalitysupporting
confidence: 59%
See 4 more Smart Citations
“…For instance, corruption can alter the composition of social spending to benefit the rich at the expense of the poor, leading to higher inequality [21]. In line with this argument, studies have found a positive relationship between institutions and income inequality.…”
Section: The Relationship Between Institutions and Inequalitysupporting
confidence: 59%
“…Based on their results, inequality appears to reduce with further reductions in the level of corruption, but only when the corruption index exceeds 2.91 (a higher corruption index indicates lower corruption levels). Similarly, Andres and Ramlogan-Dobson [21] supported the notion that there could be a trade-off between corruption and income inequality in Latin America, with a lower level of corruption leading to higher income inequality.…”
Section: The Relationship Between Institutions and Inequalitymentioning
confidence: 68%
See 3 more Smart Citations